BIOLOGICAL CONTROL OF THE COMPLEX DISEASE OF Rhizoctonia solani AND ROOT-KNOT NEMATODE Meloidogyne javanica ON CHICKPEA BY Glomus spp. AND Pseudomonas sp. - Aljuboori , Firas K.; Ibrahim, B. Y.; Mohamed , A. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Rhizoctonia-Meloidogyne complex disease is a serious problem facing legume production in many countries. The infection of chickpea (Cicer arietinum) by pathogens Rhizoctonia solani (R) and Meloidogyne javanica (M) in a single infection or combination causes severe damage to plant growth. The effect of using Glomus spp. (G) and Pseudomonas sp. (P) as a biological control agent against Rhizoctonia- Meloidogyne complex disease was tested and assessed by comparing the growth and disease parameters in infected and control plants. Chickpea growth parameters are characterized by measuring shoot and root length, and fresh and dry weight. The results of using (G) and (P) in a single treatment or in combination showed a decrease in the root gall index and in root rot disease severity when compared to the infected and healthy control treatments. The (M+ R+ G) and (M + R + G + P) combination treatment increased polyphenol oxidase (POD) and peroxidase (PPO) enzyme activity value as well as the total phenols content in treated chickpea roots. The combined effects of (G) and (P) on the pathogens’ progression and the positive effects on chickpea growth parameters are suggested to be involved in efficient disease control.